Perancangan Sistem Informasi Laundry pada CV. XYZ - Ismail; Salam, Abdus (Yayasan Kawanad, 2022)
The purpose of this research is to design an information system application for CV. XYZ to assist in handling various administrations to reporting. In recording and processing transaction data, CV. XYZ already has its own system, such as recording customer names, ordering services and shipping still using paper and the system used in recording such as data on goods washed from customers is still conventional so it is still less efficient in terms of processing time. For this reason, a computerized system is needed that is able to present data quickly and precisely so that the smooth running of business operations can be further improved. In the application development process using the PXP (Personal Extreme Programming) model. From the results of research and observations that have been made on CV. XYZ, it can be concluded; From the results of making a web-based laundry information system, it becomes easy to manage CV laundry transaction reporting. XYZ to laundry reports quickly, and can handle and control and supervise laundry transaction data, create invoices that can avoid delays and in making laundry reports for every transaction activity.